Long-Term Use of Probiotic-Containing Yogurts Is a Safe Way to Prevent Helicobacter pylori: Based on a Mongolian Gerbil's Model - Chao-Hung Kuo; Sophie S. W. Wang; Chien-Yu Lu; Huang-Ming Hu; Fu-Chen Kuo; Bi-Chuang Weng; Chun-Chieh Wu; Chung-Jung Liu; Pei-Yun Tsai; Tsung-Cheng Lee; Li-Wei Chen; Kuang-Hung Cheng; et al. (Biochemistry Research International)
Background. The suppression of Helicobacter pylori (H. pylori) decreases H. pylori-related diseases. The probiotics have an inhibitory effect on H. pylori. Aim. We investigated the effects of long-term use of yogurt on H. pylori based on Mongolian gerbils’ model. Materials and Methods. Yogurt (containing a supplement of Lactobacillus acidophilus, Bifidobacterium lactis, etc.) was used. Forty-six gerbils were divided into five groups. All groups were inoculated with H. pylori for 5 to 8 weeks. The yogurt was given as follows: Group (Gr.) A: from 1st to 4th week; Gr. B from 5th to 8th week; Gr. C: from 17th week to sacrifice; Gr. D: from 5th week to sacrifice. Gerbils were sacrificed on the 52nd week. Histology was evaluated according to the Sydney system. Results. The positive rates of H. pylori were 60% (Gr. A), 75% (Gr. B), 67% (Gr. C), 44% (Gr. D), and 100% (Gr. E). Gr. D showed lower inflammatory score. Only Gr. E (60%) had intestinal metaplasia. Gr. D showed higher IL-10 and lower TNF-α expression than Gr. E. Conclusion. Long-term intake of yogurt could decrease H. pylori infection. The long-term use of yogurt would be an alternative strategy to manage H. pylori infection.